Reporter ligand NMR screening method for 2-oxoglutarate oxygenase inhibitors. - Leung, I; Demetriades, M; Hardy, A; Lejeune, C; Smart, T; Szöllössi, A; Kawamura, A; Schofield, C; Claridge, T (2013)
The human 2-oxoglutarate (2OG) dependent oxygenases belong to a family of structurally related enzymes that play important roles in many biological processes. We report that competition-based NMR methods, using 2OG as a reporter ligand, can be used for quantitative and site-specific screening of ligand binding to 2OG oxygenases. The method was demonstrated using hypoxia inducible factor hydroxylases and histone demethylases, and K(D) values were determined for inhibitors that compete with 2OG at the metal center. This technique is also useful as a screening or validation tool for inhibitor discovery, as exemplified by work with protein-directed dynamic combinatorial chemistry.